Influence of Wastes and Synthesis Conditions on the Compressive Strength, Setting Time and Gels of Waste-Based Geopolymers - Tianyu Wang; Feng Rao; Lang Yang; Kaixi Jiang; Nanan Lin; Liwei Mo (Gels)
In civil engineering, both rapid setting and delayed setting are needed for various application scenarios. In order to regulate the setting time of concrete, the iron ore tailings-blast furnace slag (IOT-BFS)-based geopolymers were synthesized with a broad range of setting time and a high compressive strength in this study. The factors of iron ore tailings content, alkali content, liquid–solid ratio, and modulus of alkali activator on setting time of the geopolymers were analyzed. The setting times of geopolymers are tested by a manual Vicat apparatus, and their microstructure is characterized by scanning electron microscopy (SEM), as well as that the hydration heat flow is characterized by an isothermal heat conduction calorimeter (TAM Air). It is found that setting time of the geopolymers was mostly affected by the modulus of alkaline activators due to the reasons that changes in modulus lead to the accelerated hydration reaction, formation of low-polymeric silicates, generation of gels, and encapsulation of precursor particles caused by high viscosity. Adjusting the modulus of the alkaline activator to 0.8 can control the initial setting time of the geopolymers to around 3 min. When the modulus ranges from 1–1.8, the initial setting time fell in the range of 15–45 min. For an alkaline activator modulus of 2, the initial setting time increased to 108 min. This study gives a clue for the preparation of geopolymers with adjustable setting times for multi-scenario applications in construction materials.